An Experimental Investigation on the Effect of Sintering Temperature and Holding Time to the Characteristics of Fecual Powder Compacts Formed at Elevated Temperature - Rahman, M. M.; Ismail, M. A.; Rahman, H. Y. (International Journal of Engineering and Technology, 2018)
This paper presents the experimental investigation on the effect of sintering schedule to the final properties of FeCuAl powder compacts formed at elevated temperature through a lab-scale uniaxial die compaction rig. Â Iron (Fe) powder ASC100.29 was used as a main powder constituent and mixed with elemental powders which are copper (Cu) and aluminum (Al). Â The weight percentage of powder mass was divided into four, i.e., iron (91.7 wt%), copper (7.5 wt%), aluminum (0.5 wt%), and zinc stearate (0.3 wt%) as lubricant. Â All the powders were mixed through mechanical blending at a rotation speed of 30 rpm for 30 min. Â The mixed powder mass was compacted at 150ËšC by 425 MPa of axial loading from upward and downward simultaneously. Â Subsequently, the defect-free green compacts were sintered under controlled argon gas atmosphere at three different sintering temperatures, i.e., 800ËšC, 900ËšC and 1000ËšC for 120 min, 150 min and 180 min, respectively at constant sintering rate of 10ËšC/min. Â Afterwards, the sintered samples were characterized for their physical properties, electrical properties, mechanical properties and their microstructures were evaluated. Â The results revealed that higher flexure stress was acquired by sample sintered at 1000ËšC for 120 min and their microstructures were found to be better, i.e., the particles were bonded perfectly.